Effects of atrophine sulphate, xylazine hydrochloride, ketamine hydrochloride and diazepam in cats - Haque, Md Mahfuzul; Lucky, Nasrin Sultana (Research in Agriculture Livestock and Fisheries, 2019)
In this experiment eighteen (18) apparently healthy female cats were assigned in three anesthetic groups to attain the objectives of assess the efficacy and adverse effects of anesthetic agents. The body weight of the cats ranged from 2.5 to 3 kg and 8 to 12 months of age. There were divided into following three groups; A: atropine sulphate (0.04 mg/kg), xylazine hydrochloride (1 mg/kg) and Ketamine hydrochloride (5 mg/kg) body weight intramuscularly, B: xylazine hydrochloride (1 mg/kg) and ketamine hydrochloride (5 mg/kg) body weight intramuscularly and C: ketamine hydrochloride (5 mg/kg) and diazepam (1.4 mg/kg) body weight intramuscularly. The mean of induction period was significantly (P<0.05) shorter in Group A and B. Duration of anesthesia, time to first movement there was no difference among these three groups. The induction period was 2.67±0.82, 3.17±0.75 and 13±2.28, Duration of anesthesia was 34.17±2.40, 39.33±1.75 and 35.33±2.73, Time to first movement was 7.5±1.52, 6.67±1.03 and 7±0.894, Time to sternal position was 10.67±1.21, 10.33±1.03 and 19.83±2.07, Time to standing position was 14.67±2.07, 14.33±1.51 and 26.22±2.61 respectively in case of Group A, Group B and C. The induction, duration and recovery period from anesthesia was smooth in atropine sulphate-xylazine-ketamine hydrochloride combination. Salivation was found in xylazine-ketamine hydrochloride combination. Vomition observed onset of action and salivation during recovery period in Ketamine hydrochloride-Diazepam combination. From this study it was found that atropine sulphate-xylazine-ketamine hydrochloride does not show any adverse effect on cat and is an identical satisfactory anesthetic combination which will be helpful for performing any surgical interventions for cats. Res. Agric., Livest. Fish.6(1): 127-132, April 2019